Effects of donepezil on the amplitude of low-frequency fluctuations in the brain of patients with Alzheimer's disease: evidence from resting-state functional magnetic resonance imaging. Issue 11 (4th August 2021) - Yang, Hua; Zhang, Jiangtao; Cheng, Jianan
Abstract : Objectives: To monitor the effects of donepezil on spontaneous neuronal activity (SNA), and the mechanisms underlying these effects in patients with mild-to-moderate Alzheimer's disease, using the amplitude of low-frequency fluctuations (ALFFs), a metric of resting-state functional MRI (rs-fMRI). Methods: Eleven patients with Alzheimer's disease were treated with donepezil for 6 months. Before and after treatment, the Mini-Mental State Examination (MMSE), Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-cog), Clinical Dementia Rating (CDR), Neuropsychiatric Inventory and Activities of Daily Living scores, along with rs-fMRI of patients were assessed. Eleven age-, sex-, and education-matched controls underwent MMSE and CDR assessments and rs-fMRI at enrollment. The ALFFs of the whole brain were obtained and compared between the groups. Results: Following donepezil treatment, MMSE scores increased ( P = 0.043) and ADAS-cog scores decreased ( P = 0.010). Regarding SNA post-treatment, ALFF increased significantly in the right triangular part of the inferior frontal gyrus (IFGtriang; P = 0.030; d = −0.595) and the right orbital part of the inferior frontal gyrus ( P = 0.044; d = −0.628) and decreased significantly in the left medial orbital part of the superior frontal gyrus ( P = 0.039; d = 0.606) and the right gyrus rectus ( P = 0.010; d = 0.609). Furthermore, the changes in ADAS-cog scores from before to after treatment were positively correlated with the changes in ALFF in the right IFGtriang ( r = 0.645; P = 0.032). Conclusions: Donepezil improved SNA in the frontal lobe of patients with Alzheimer's disease. Therefore, ALFF was demonstrated to be a potential tool for assessing the effectiveness of Alzheimer's disease treatment.